S.L. Simpson Gallery 1980-1990. - Grenville, Bruce; Dewdney, Christopher (Toronto : S.L. Simpson Gallery, 1990)
Alexander, Shelagh ; Boigon, Brian ; Clarkson, David ; Davis, Christine ; Doyle, Judith ; Lebredt, Gordon ; Mcnealy, Robert ; Patton, Andy ; Schwarz, Judith ; Spero, Nancy ; Tomas, Dave ; Van Halm, Renee ; Wainio, Carol ; Walker, Douglas ; White, Carolyn
Documenting activities from 1980 to 1990, Grenville follows the formation of a postmodern practice in the Toronto art community. Dewdney's textual collage combines the history of the Gallery with critical commentary. Includes an interview with Simpson as well as a chronology of exhibitions. Brief notes on contributors.
Engels
boek